Kinetics and Activation Complex Thermodynamic Study of the Acidity Removal of Oleic Acid via Esterification Reaction on Commercial 13X Zeolite - Jurmot, Shahad; Abbas, Ammar S. (Iraqi Journal of Chemical and Petroleum Engineering, 2022)
The study involved the removal of acidity from free fatty acid via the esterification reaction of oleic acid with ethanol. The reaction was done in a batch reactor using commercial 13X zeolite as a catalyst. The effects of temperatures (40 to 70 °C) and reaction time (up to 120 minutes) were studied using 6:1 mole ratio of pure ethanol to oleic acid and 5 wt. % of the catalyst. The results showed that acid removed increased with increasing temperature and reaction time. Also, the acidity removal rises sharply during the first reaction period and then changes slightly afterward. The highest acidity removal value was 67 % recorded at 110 minutes and 70 °C. An apparent homogeneous reversible reaction kinetic model has been proposed and solved with the experimentally obtained kinetics data to evaluate reaction rate constants versus temperature, pre-exponential factors, and activation energy values for the forward and the backward esterification reactions. The activation energies were 34.863 kJ/mol for the forward reaction and 29.731 kJ/mol for the backward reaction. The thermodynamics of the activation step of the forward and reverse reactions was studied based on the hypothesis of forming a complex material that decomposes into a product. The activation steps were studied using Eyring bimolecular collision theory approach, and both ΔH* and ΔS* were determined for forward and backward esterification reactions. The enthalpies of activation were 32.141 kJ/mol and 27.080 kJ/mol for the forward reaction and the backward reaction, and the entropies of activation were - 193.7 and -212.7 J/mol. K for the forward reaction and the backward reaction, respectively.